Circulating T Cell Activation and Exhaustion Markers Are Associated With Radiation Pneumonitis and Poor Survival in Non-Small-Cell Lung Cancer - Berg, Janna; Halvorsen, Ann Rita; Bengtson, May-Bente; Lindberg, Morten; Halvorsen, Bente; Aukrust, Pål; Helland, Åslaug; Ueland, Thor (Frontiers in Immunology, 2022)
Introduction Persistent inflammation and immune activation in the lungs are associated with adverse outcomes such as radiation pneumonitis (RP) and poor survival in non-small-cell lung cancer (NSCLC) patients. However, it is unknown how this is reflected by leukocyte activation markers in serum. Objective The aim was to evaluate the serum levels of activation of different leukocyte subsets and to examine those in relation to the pathogenesis of RP and survival in NSCLC. Methods We analyzed the serum levels of MPO, sCD25, sTIM-3, sPD-L1, sCD14, sCD163, CCL19 and CCL21 in 66 inoperable NSCLC patients with stage IA-IIIA disease. The patients were treated with stereotactic body radiation therapy (SBRT) or concurrent chemoradiation therapy (CCRT), followed by regular blood sampling for 12 months after treatment and for 5 years for survival. Results Nineteen (29%) patients developed RP, which occurred more frequently and earlier in patients receiving CCRT than in those receiving SBRT. Increases in sCD25, sTIM-3 and CCL21 levels were observed at the last 6 months of follow-up in patients who had RP after SBRT. Patients who had RP after CCRT had higher sTIM-3 levels during the first 3 months of follow-up. Baseline sCD25 was independently associated with both 2- and 5-year mortality outcomes, while baseline sTIM-3 was independently associated with 2-year mortality. Conclusion We showed that T cell activation and exhaustion markers such as sCD25 and sTIM-3 are enhanced in patients developing RP and are associated with poor survival in NSCLC.